∫3x9x−1dx is equal to

3x9x1dx is equal to

  1. A

    1log3log3x+9x1+C

  2. B

    1log3log9x+9x1+C

  3. C

    1log9log3x+9x1+C

  4. D

    1log9log3x9x1+C

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    Let I=3x9x1dx=3xdx3x21

    put ,3x=t3xlog3dx=dt3xdx=dtlog3

     I=1log3dtt21=1log3logt+t21+C=1log3log3x+9x1+C

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.